Methemoglobinemia and Delayed Encephalopathy After 5-Bromo-2-Nitropyridine Poisoning: A Rare Case Report - Shi, Longke; Yu, Guangcai; Zhao, Liwen; Wen, Zixin; Li, Yaqian; Kan, Baotian; Jian, Xiangdong (Frontiers in Public Health, 2022)
An intermediate in the synthesis of pharmaceutical and pesticide products, 5-bromo-2-nitropyridine is toxic to the human body. However, the 5-bromo-2-nitropyridine poisoning have not been previously reported. Here, we report the case of a 40-year-old man who suffered skin exposure to leaked 5-Bromo-2-nitropyridine at work. After exposure, the patient rapidly developed dizziness, fatigue, nausea, vomiting, diffuse cyanosis, and coma. Methemoglobinemia, hemolytic anemia, rhabdomyolysis, and acute renal failure were observed after admission. He improved markedly after treatment but delayed encephalopathy was confirmed 82 days after the exposure. This case highlights that 5-bromo-2-nitropyridine can absorb through the skin, resulting in methemoglobinemia and delayed encephalopathy.